UPAYA MENINGKATKAN HASIL BELAJAR IPS SISWA MELALUI PENGGUNAAN MEDIA PETA DI KELAS V SD NEGERI 004 BUKIT DATUK DUMAI - ', Herlina (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe the learning outcomes through the use of media map. Thesubjects were students of class V SD 004 Bukit Datuk Dumai consisting of two cycles.Improved learning outcomes in terms of four categories, namely absorption, the effectivenessof learning, mastery learning completeness students both individual and classicalcompleteness and thoroughness of learning outcomes. The instrument used for data collectionis an oral test and a written test in the form of worksheets that do after the learning process.Results showed absorption learning outcomes on average 83% categorized as very good, veryeffective learning effectiveness categorized by an average of 8.5. While completeness ofstudent learning outcomes otherwise completed 100%.